The effects of experimental freeze-thaw cycles to bone as a component of subaerial weathering. (April 2016) - Pokines, James T.; King, Rebecca E.; Graham, Deborah D.; Costello, Amanda K.; Adams, Donovan M.; Pendray, Jennifer M.; Rao, Kushal; Siwek, Donald
Abstract: Subaerial weathering of bone is a taphonomic process that affects many archaeological and paleontological assemblages and is characterized by surface bleaching, loss of organic component, and progressive cracking and fragmentation of the bone surfaces. The mechanisms by which these changes occur, however, are poorly understood but are hypothesized to include ultraviolet exposure, degreasing, leaching, remineralization, wetting/drying, thermal expansion/contraction, and freezing/thawing. In order to examine the potential contribution of the latter process to weathering, a sample ( n  = 93) of naturally decomposed and degreased metapodials of white-tailed deer ( Odocoileus virginianus ) were subjected to up to 75 cycles of complete freezing and thawing under laboratory conditions, with samples withdrawn each 25 cycles for histological examination of the taphonomic alterations to the bone microstructure. Macroscopic and microscopic changes included progressive cracking that parallels part of the progressive degradation of weathered bone, but no elements unequivocally reached weathering stage 1 over this interval. Highlights: An initial sample ( n  = 93) of Odocoileus virginianus bones were subjected to up to 75 complete freeze-thaw cycles. Bones were examined macroscopically and microscopically. Surface weathering did not advance to weathering stage 1, but increases in overall cracking were found. Freeze-thaw may be an important component of the overall osseous weathering process.